Examination of the Effect of Concrete Crosstie Rail Seat Deterioration on Rail Seat Load Distribution. Issue 1 (January 2015) - Greve, Matthew J.; Dersch, Marcus S.; Edwards, J. Riley; Barkan, Christopher P. L.; Thompson, Hugh; Sussmann, Theodore R.; McHenry, Michael T.
One of the more critical failure modes of concrete crossties in North America is the degradation of the concrete surface at the crosstie rail seat, also known as rail seat deterioration (RSD). Loss of material beneath the rail can lead to wide gage, cant deficiency, reduced clamping force of the fastening system, and an increased risk of rail rollover. Previous research conducted at the University of Illinois at Urbana–Champaign (UIUC) identified five primary failure mechanisms associated with RSD: abrasion, crushing, freeze–thaw damage, hydroabrasive erosion, and hydraulic pressure cracking. Because the magnitude and distribution of load applied to the rail seat affects four of these five failure mechanisms, effectively addressing RSD requires an understanding of the factors affecting rail seat load distribution. As part of a larger study aimed at improving concrete crossties and fastening systems, UIUC researchers are attempting to characterize the loading environment at the rail seat by using matrix-based tactile surface sensors (MBTSS). This instrumentation technology has been implemented in both laboratory and field environments and has provided valuable insight into the distribution of a single load over consecutive crossties. This paper focuses on the analysis of data gathered from MBTSS experiments designed to explore the effect of manufactured RSD on the load distribution and pressure magnitude at the rail seat. The knowledge gained from these experiments will be integrated with associated research conducted at UIUC to form the framework for a mechanistic design approach for concrete crossties and fastening systems.